A situação atual da psicologia na educação: a presença da ciência e da tecnologia - Oliveira, Tiago Lopes de (2013)
This work aims to contribute to a process of reflection on the current situation of psychology in the education field and aims to investigate: a) that psychological theories are prevalent in this area of study, b) how these theories can be used in researches that link psychology and education. The study was founded on the description of the objective structure of industrial society and its concerning rationality, containing a discussion about the relationship between science and technology. With the purpose of collecting data about the object of this study was elaborated a discussion about the development of psychology in the education field, focused on the development of educational psychology and scholastic and on the theoretical foundation of psychology in education. It was also prepared a survey with the CAPES Bank of Thesis in order to better understand the presence of psychological theories in education. Finally, we performed the analysis of two doctoral theses in order to demonstrate the possible uses of psychological theories in education. To establish the analyzes, we focus mainly on the concepts of science and technology, technological rationality, training and industrial society presented by the authors of critical theory: Adorno, Horkheimer and Marcuse. In this research we found that there are currently, in the field of education, a trend of prevalence of psychological theories that consider fundamental in their analyzes historical and social aspects implicated in the process of formation of the individual. We note, however, that the transforming potential of these theories also depends on the way they are perceived in the polls. Finally, we conclude that currently in education the psychology begins to show greater concern with the social and historical aspects of the educational process at the expense of a more individualistic vision. And this fact favors the development of psychology as science in education